Characterizations on fracture process zone of plain concrete - Tang, Yuxiang; Chen, Hongniao (Journal of Civil Engineering and Management, 2019)
The fracture property of concrete is essential for the safety and durability analysis of concrete structures. Investigating the characteristics of the fracture process zone (FPZ) is of great significance to clarify the nonlinear fracture behaviour of concrete. Experimental and numerical investigations on the FPZ of plain concrete in pre-notched beams subjected to three-point bending were carried out. Electronic speckle pattern interferometry (ESPI) technique was used to observe crack evolution and measure the full-field deformation of the beams. The development of the FPZ were evaluated qualitatively and quantitatively based on the in-plane strain contours and displacement field measured by ESPI, respectively. By integrating the cohesive crack model and finite element (FE) model, various tension softening curves (TSCs) were employed to simulate the fracture response of concrete beams. By comparing the deformation obtained by FE simulation and experiments, the TSCs of plain concrete were evaluated and most suitable TSCs of concrete were recommended.